2015
DOI: 10.1097/qai.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Antigen Screening and Early Antifungal Treatment to Prevent Cryptococcal Meningitis

Abstract: Although limited, the body of evidence regarding CrAg screening and treatment suggests that the intervention may have an impact on preventing cryptococcal meningitis and death in persons with AIDS. Additional research is needed to quantify the intervention's effectiveness and identify optimal treatment dosing and implementation best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 27 publications
(40 reference statements)
0
40
0
Order By: Relevance
“…This might be supported by genotyping studies that dealt with the ubiquitous nature of Cryptococcus species providing strong evidence for additional origins of exposure like different species of plants, soil, and house dust (Chen et al, 2015;Cogliati, 2013 & Harrison, 2010;Makadzange & McHugh, 2014). In addition to this, those that were hospitalized for different reasons were at a significant risk of cryptococcal infections (Kaplan et al, 2015). In this study, higher prevalence of CrAg was observed in peoples with advanced immune-suppression, which is supported by other similar studies, and WHO recommendations (Alemu et al, 2013;Ganiem et al, 2014;Osazuwa et al, 2012;Pongsai et al, 2010;Randhawa et al, 2011;Sawadogo et al, 2016;Smith et al, 2013;World Health Organization, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This might be supported by genotyping studies that dealt with the ubiquitous nature of Cryptococcus species providing strong evidence for additional origins of exposure like different species of plants, soil, and house dust (Chen et al, 2015;Cogliati, 2013 & Harrison, 2010;Makadzange & McHugh, 2014). In addition to this, those that were hospitalized for different reasons were at a significant risk of cryptococcal infections (Kaplan et al, 2015). In this study, higher prevalence of CrAg was observed in peoples with advanced immune-suppression, which is supported by other similar studies, and WHO recommendations (Alemu et al, 2013;Ganiem et al, 2014;Osazuwa et al, 2012;Pongsai et al, 2010;Randhawa et al, 2011;Sawadogo et al, 2016;Smith et al, 2013;World Health Organization, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…From the sign and symptoms, nausea and vomiting were observed in most of the participants tested positive in contrary to other studies (Hashimoto e Souza et al, ; Jarvis, Meintjes, Williams, Rebe, & Harrison, ; Makadzange & McHugh, ). In addition to this, those that were hospitalized for different reasons were at a significant risk of cryptococcal infections (Kaplan et al, ). In this study, higher prevalence of CrAg was observed in peoples with advanced immune‐suppression, which is supported by other similar studies, and WHO recommendations (Alemu et al, ; Ganiem et al, ; Osazuwa et al, ; Pongsai et al, ; Randhawa et al, ; Sawadogo et al, ; Smith et al, ; World Health Organization, ).…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening sCrAg has been advocated for HIV‐infected patients at entry into care and prior to antiretroviral therapy in areas with high rates of cryptococcal infection . Whether similar baseline screening should be applied to patients on chemotherapy has not previously been explored in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, persons with CD4 cell counts ≤100 cells/ μ l have a reported CRAG prevalence between 2.2% and 21% with an average of 6.8% (95%CI, 6.5–7.2%) in studies including only asymptomatic, ART‐naïve outpatients . In Southeast Asia, CRAG prevalence in asymptomatic ART‐naïve persons with CD4 cell counts ≤100 cells/ μ l is reported in 4–12.9% . The WHO recommends CRAG screening in high prevalence regions, defined as ≥3% based CRAG‐latex agglutination and the cost of amphotericin therapy alone , but other analyses have reported that screening may be cost‐effective even at a prevalence as low as 1% based on the lower cost of CRAG LFA compared to the traditional latex agglutination CRAG .…”
Section: Discussionmentioning
confidence: 99%